Understanding the Health Landscape of Coastal Communities: A Review on Non-Communicable Diseases - Maziyya, Nur; Nurhamsyah, Donny (Universitas Padjadjaran, 2025)
Non-communicable diseases (NCDs), particularly hypertension and type 2 diabetes mellitus, pose serious health challenges in coastal communities, which are often socioeconomically and geographically vulnerable. Limited access to healthcare and inadequate preventive health information further worsen these issues. This literature review aims to describe the health profile and associated risk factors of NCDs in coastal populations. A structured search was conducted through PubMed, Google Scholar, and ScienceDirect using keywords including non-communicable diseases, hypertension, diabetes, coastal community, and risk factors. Inclusion criteria comprised peer-reviewed primary research (quantitative or qualitative), published in English or Indonesian between 2020 and 2025. Of 67 articles identified, 17 met the criteria and were analyzed descriptively. Hypertension emerged as the most frequently studied NCD, followed by diabetes and metabolic syndrome. Commonly reported risk factors included obesity, low physical activity, high sodium intake, smoking, stress, aging, and low socioeconomic status. Some studies also noted the influence of seafood consumption, sleep quality, and comorbid conditions. Among elderly populations, factors such as health insurance and access to health counseling influenced health-seeking behaviors. These findings highlight the urgent need for tailored, community-based strategies to prevent and control NCDs in coastal regions.